Gene Therapy Potential for Genetic Disorders of Surfactant Dysfunction - Cooney, Ashley L.; Wambach, Jennifer A.; Sinn, Patrick L.; McCray, Paul B. (Frontiers in Genome Editing, 2022)
Pulmonary surfactant is critically important to prevent atelectasis by lowering the surface tension of the alveolar lining liquid. While respiratory distress syndrome (RDS) is common in premature infants, severe RDS in term and late preterm infants suggests an underlying genetic etiology. Pathogenic variants in the genes encoding key components of pulmonary surfactant including surfactant protein B (SP-B, SFTPB gene), surfactant protein C (SP-C, SFTPC gene), and the ATP-Binding Cassette transporter A3 (ABCA3, ABCA3 gene) result in severe neonatal RDS or childhood interstitial lung disease (chILD). These proteins play essential roles in pulmonary surfactant biogenesis and are expressed in alveolar epithelial type II cells (AEC2), the progenitor cell of the alveolar epithelium. SP-B deficiency most commonly presents in the neonatal period with severe RDS and requires lung transplantation for survival. SFTPC mutations act in an autosomal dominant fashion and more commonly presents with chILD or idiopathic pulmonary fibrosis than neonatal RDS. ABCA3 deficiency often presents as neonatal RDS or chILD. Gene therapy is a promising option to treat monogenic lung diseases. Successes and challenges in developing gene therapies for genetic disorders of surfactant dysfunction include viral vector design and tropism for target cell types. In this review, we explore adeno-associated virus (AAV), lentiviral, and adenoviral (Ad)-based vectors as delivery vehicles. Both gene addition and gene editing strategies are compared to best design treatments for lung diseases resulting from pathogenic variants in the SFTPB, SFTPC, and ABCA3 genes.